“Early Mathematical Competence Test-R”: A Multimedia Tool for Assessing the Early Mathematical Competence - Araujo, Antonio M.; Ruiz, Gonzalo; Aguilar, Manuel; Aragón, Estibaliz L.; Navarro, José I. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
Using a computerized task as an assessment procedure may have advantages over the pencil-and-paper tradi-tionalway. The motivational variable associated to computerized tasks can involve a higher functionality results. Com-puterized tool also can measure a higher range of variables such as response time, error and correct responses, etc. We present the Early-Numeracy-Test-R adapted from a paper and pencil assessment tool. In amultimedia environment, we assessed several components involved in the development of mathematical competence in school-age children of 4-7 years. This kind of measurement provides information about the relational and cognitive components implicit in early mathematical development. It also allowed prediction for children in risk of mathematical learning difficulties. This may encourage processes of prevention and early intervention of mathematical learning difficulties. The tool was developed in a multimedia environment in Flash, using Php for storing data.